Grammatical Archaisms in the New Latin Poetry of Ukraine of the Early Modern Period: the Invariance of Forms and Functions - Кощій, Оксана Миколаївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
The article examines the use of grammatical archaisms in the New Latin poetic text based on the historical poem by Simon Pekalid De bello Ostrogiano (Krakow, 1600). It consistently reflects one of the most important properties of poetic speech – the implementation of phonetic-grammatical and lexical-word-formation capabilities of the language system and it clearly shows the dynamic nature of language elements at all levels of Latin. It is determined that the main factors that influenced the adoption of grammatical archaisms were the metric requirements and stylistic canons of the ancient epic. Due to the functions performed in the poetic sphere, the early modern Latin, which owes a flexible language system with a grammatical basis preserved from classical Latin, was characterised by significant variability of the language structure due to the presence of elements of different origin. Belonging to the passive vocabulary of the language, in most cases archaic vocabulary was stylistically marked and it often passed into the category of traditionally poetic. The tradition of the epic genre and the stylistic differentiation of various variants of speech suggested the presence in the epic text of a certain number of archaic morphological forms, as a result of which the stylistic differentiation of inflections-doublets arose in Latin, one of which was archaic. The functioning of archaic forms in the New Latin poetic text has a dual character: as a linguistic unit, archaisms occupy a special place within synchronous relations, but as a stylistic unit they are decoded according to the second, i.e. earlier system of literary language. The use of multi-temporal morphological forms is associated with their poetic function in the language, which has gradually produced certain stylistic norms in the use of grammatical forms over the centuries.